Low latitude troposphere: a preliminary study using GPS CORS data in South East Asia - Musa, Tajul A. (Omnipress, USA, 2005)
Hot and wet conditions in the equatorial or low latitude region degrade satellite positioning accuracy noticeably. The degradation is related to the strong tropospheric effect, especially the wet component which is approximately proportional to the content of water vapor in the troposphere and thus makes satellite positioning more challenging in this region. Despite the efforts to achieve better understanding of the signal delay in the low latitude troposphere, much more still remains to be improved. Knowing that the water vapor content is heavy in this region, it is of special interest for meteorologists to look into the tropospheric effect. Such knowledge is vital for understanding the global climate, whereas a short term variation of water vapor is very useful input to local weather forecasting. South-East Asia is selected in this study to investigate the effect of regional tropospheric delay, and broadly to understand the behavior of a low latitude troposphere. The study area covers Malaysia and Singapore where GPS CORS networks have already been established. Results from GPS data processing show that a wide variation of the tropospheric delay can be observed. As expected, the largest variation occurs during the North-East monsoon (November to early March) and the South-West monsoon (early May to August). Coordinate repeatabilities of the sites in the network are calculated to show the impact of the tropospheric delay on the precision of GPS positioning activities. In addition, the variations of the tropospheric delay estimated from a local and a regional GPS network are compared to the results from the global network.